Coupled Thermo-Hydro-Mechanical-Chemical (THMC) Responses of Ontario’s Host Sedimentary Rocks for Nuclear Waste Repositories to Past and Future Glaciations and Deglaciations - Nasir, Othman (Université d'Ottawa / University of Ottawa, 2013)
Glaciation is considered one of the main natural processes that can have a significant impact on the long term performance of DGRs. The northern part of the American continent has been subjected to a series of strong glaciation and deglaciation events over the past million years. Glacial cycles cause loading and unloading, temperature changes and hydraulic head changes at the ground surface. These changes can be classified as transient boundary conditions. It is widely accepted that the periodic pattern of past glacial cycles during the Late Quaternary period are resultant of the Earth’s orbital geometry changes that is expected to continue in the future. Therefore, from the safety perspective of DGRs, such probable events need to be taken into account. The objective of this thesis is to develop a numerical model to investigate the thermo-hydro-mechanical-chemical (THMC) coupled processes that have resulted from long term past and future climate changes and glaciation cycles on a proposed DGR in sedimentary rocks in southern Ontario. The first application is done on a large geological cross section that includes the entire Michigan basin by using a hydro-mechanical (HM) coupled process. The results are compared with field data of anomalous pore water pressures from deep boreholes in sedimentary rocks of southern Ontario. In this work. The modeling results seem to support the hypothesis that at least the underpressures in the Ordovician formation could be partially attributed to past glaciation. The second application is made on site conditions by using the THMC model. The results for the pore water pressure, tracer profiles, permafrost depth and effective stress profile are compared with the available field data, the results show that the solute transport in the natural limestone and shale barrier formations is controlled by diffusion, which provide evidence that the main mechanism of transport at depth is diffusion-dominant. The third application is made on site conditions to determine the effect of underground changes in DGRs due to DGR construction. The results show that future glaciation loads will induce larger increases in effective stresses on the shaft. Furthermore, it is found that hypothetical nuclide transport in a failed shaft can be controlled by diffusion and advection. The simulation results show that the solute transported in a failed shaft can reach the shallow bedrock groundwater zone. These results might imply that a failed shaft will substantially lose its effectiveness as a barrier. The fourth application is proposed to investigate the geochemical evolution of sedimentary host rock in a near field scale. In this part, a new thermo-hydro-mechanical-geochemical simulator (COMSOL-PHREEQC) is developed. It is anticipated that there will be a geochemical reaction within the host rock that results from interaction with the water enriched with the CO2 generated by nuclear waste.